Rainbow Coloring of Magic Fuzzy Random Graphs - Abirami, R.; Sarala, N. (Communications in Mathematics and Applications, 2024)
This study introduces the concept of rainbow coloring to magic fuzzy random graphs, which combine the properties of fuzzy random graphs and magic graphs. A comprehensive study of rainbow coloring is presented in this study, which explores fundamental properties and computational issues. Also, it explores the role of rainbow coloring in magic fuzzy random graph connectivity and robustness, provides insights into the interaction between graph coloring and structure. Rainbow coloring is inherently theoretical and this finding contributes to our understanding of network design and distributed systems as well.
Keywords: Fuzzy random graph; Labeling of a fuzzy random graph; Magic labeling of a fuzzy random graph; Rainbow coloring